PENGARUH MODEL KOOPERATIF LEARNING TIPE (STAD) BERBASIS MEDIA QUESTION BOX PADA PEMBELAJARAN IPAS TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V SD - Ika Saefitri; Fadhilah Khairani; Muhisom; Deviyanti Pangestu (STKIP Subang, 2025)
The problem in this study was the low learning outcomes of fifth-grade students in the IPAS subject at SD N 2 Palapa. This study aimed to determine the effect of the ooperative learning model type (STAD) assisted by question box media on IPAS learning outcomes of fifth-grade students. The method used was a quasiexperimental method with a non-equivalent control group design. Data collection techniques in this study used multiple-choice tests and non-test observations. The research sample was determined using a non-probability sampling technique, with a total population and sample of 57 students. The sample was selected using purposive sampling. The data were analyzed using a Simple Regression Test, with the results showing Fcount > Ftable, namely 56.118 > 4.225. The significance value obtained was 0.001 < 0.05, thus it could be concluded that there was an effect of the cooperative learning model type (STAD) based on question box media in IPAS learning on the learning outcomes of fifthgrade students